Upaya Penurunan Nyeri Pada Pasien Tn.M Dengan Post Orif Fraktur Radius Sinistra - Dwi Cahyo, Galih; , Fahrun Nur Rosyid, S. Kep, Ns, M. Kes (2017)
ABSTRACT Fractures is an interruption of continuity condition of bone tissue and / or cartilage which is generally caused by rudapaksa.Trauma that causes bones to fracture can be either direct trauma and trauma indirectly. one of the most prominent clinical manifestations in patients with fracture is pain. Pain is a sensory experience emosioonal and unpalatable akkibat actual tissue damage and potential. Pain occurs when simultaneously with the occurrence of the disease process or simultaneously with the treatment process. deep breathing relaxation technique is one of the non-pharmacological methods of pain management to nurses provide nursing diagnoses of patients with pain. The main purpose of execution of the writing of this scientific publication is to enable authors to understand and perform management of pain in patients with problems post ORIF Tn.M fracture of the left. The method used is descriptive method with case study approach that the nursing care of patients post Orif fracture of the left radius begins with an assessment, intervention, implementation and evaluation of nursing. And get the results in after care for 3 x 24 hour decrease pain scale is evidenced by pain scale on the third day of the original scale of 6 to 2. The conclusion of the study conducted found that deep breathing relaxation technique is one of the non-pharmacological methods of pain management effective to reduce pain. Keywords: Fracture, Pain, Non-pharmacological measures.